Identification of miRNAs and their targets in wild tomato at moderately and acutely elevated temperatures by high-throughput sequencing and degradome analysis - Zhou, Rong; Wang, Qian; Jiang, Fangling; Cao, Xue; Sun, Mintao; Liu, Min; Wu, Zhen (Scientific reports, 2016)
MicroRNAs (miRNAs) are 19–24 nucleotide (nt) noncoding RNAs that play important roles in abiotic stress responses in plants. High temperatures have been the subject of considerable attention due to their negative effects on plant growth and development. Heat-responsive miRNAs have been identified in some plants. However, there have been no reports on the global identification of miRNAs and their targets in tomato at high temperatures, especially at different elevated temperatures. Here, three small-RNA libraries and three degradome libraries were constructed from the leaves of the heat-tolerant tomato at normal, moderately and acutely elevated temperatures (26/18 °C, 33/33 °C and 40/40 °C, respectively). Following high-throughput sequencing, 662 conserved and 97 novel miRNAs were identified in total with 469 conserved and 91 novel miRNAs shared in the three small-RNA libraries. Of these miRNAs, 96 and 150 miRNAs were responsive to the moderately and acutely elevated temperature, respectively. Following degradome sequencing, 349 sequences were identified as targets of 138 conserved miRNAs, and 13 sequences were identified as targets of eight novel miRNAs. The expression levels of seven miRNAs and six target genes obtained by quantitative real-time PCR (qRT-PCR) were largely consistent with the sequencing results. This study enriches the number of heat-responsive miRNAs and lays a foundation for the elucidation of the miRNA-mediated regulatory mechanism in tomatoes at elevated temperatures.